2011
DOI: 10.1164/rccm.201010-1629oc
|View full text |Cite
|
Sign up to set email alerts
|

Bronchial Secretory Immunoglobulin A Deficiency Correlates With Airway Inflammation and Progression of Chronic Obstructive Pulmonary Disease

Abstract: Our findings indicate that epithelial structural abnormalities lead to localized SIgA deficiency in COPD airways. Impaired mucosal immunity may contribute to persistent airway inflammation and progressive airway remodeling in COPD.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

11
132
2

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 114 publications
(149 citation statements)
references
References 49 publications
11
132
2
Order By: Relevance
“…In 2001, Pilette and coworkers (13) reported that secretory component expression is reduced in airways of patients with COPD. Subsequently, we showed that pIgR expression is down-regulated in COPD and that airway surface SIgA deficiency is widespread in COPD and correlates with severity of airflow obstruction (14,15). Consistent with these observations, cultured airway epithelial cells from patients with COPD were reported to express lower levels of pIgR than airway epithelial cells from healthy control subjects (16).…”
supporting
confidence: 55%
“…In 2001, Pilette and coworkers (13) reported that secretory component expression is reduced in airways of patients with COPD. Subsequently, we showed that pIgR expression is down-regulated in COPD and that airway surface SIgA deficiency is widespread in COPD and correlates with severity of airflow obstruction (14,15). Consistent with these observations, cultured airway epithelial cells from patients with COPD were reported to express lower levels of pIgR than airway epithelial cells from healthy control subjects (16).…”
supporting
confidence: 55%
“…Diseased epithelium was unable to transport adequate amounts of secretory immunoglobulin A (SIgA), particularly in advanced disease associated with stratified squamous epithelial metaplasia. This study also found that proportion of patients with COPD harbouring latent viral agents was significantly higher than in control subjects and that 90% of virally infected airways were surface IgA deficient in COPD airways [Polosukhin et al 2011]. This highlights the possible role of mucosal pathology in contributing to the defective immunity to viruses, even in the context of an adequate systemic antibody response.…”
Section: Copd and The Immune Systemsupporting
confidence: 52%
“…This observation is probably related to reduced pIgR-mediated transport of IgA across the epithelium, which has been reported in COPD [2,5], and may abort IgA trafficking across the respiratory mucosa and limit its role for so-called immune exclusion of inhaled pathogens. In addition, although in vitro exposure of the epithelium to cigarette smoke could upregulate IL-6 release and TACI expression, it counteracted the IgA-promoting effect of the epithelium on B cells.…”
Section: Both Maturation Of B-cells Into Cd38mentioning
confidence: 91%
“…We previously showed that patients with severe COPD display decreased bronchial pIgR expression [2], and this defect correlated with disease severity and neutrophilic inflammation [3,4]. It was also shown that this impaired transport of IgA could not only result in impaired mucosal immunity but also in the formation of immune complexes in subepithelial tissues [5].…”
Section: Introductionmentioning
confidence: 97%